2017
DOI: 10.1177/1179554917713005
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of [18Fluorine]-Fluoro-2-Deoxy-d-Glucose Positron Emission Tomography-Computed Tomography Response Assessment Following (Chemo)radiotherapy for Locally Advanced Laryngeal/Hypopharyngeal Carcinoma

Abstract: INTRODUCTIONThe accuracy of response assessment positron emission tomography (PET)-computed tomography (CT) following radiotherapy with or without chemotherapy for laryngeal/hypopharyngeal squamous cell carcinoma is uncertain.METHODSIn all, 35 patients with laryngeal or hypopharyngeal squamous cell carcinoma who were treated between 2009 and 2014 with (chemo)radiotherapy were identified. The accuracy of response assessment PET-CT was made by correlation with clinical follow-up and pathological findings.RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…When there is doubt about clinical and radiological response a 'second-look' PET-CT can be used to spare patients unnecessary surgical intervention Introduction Accurate response assessment following (chemo)radiotherapy for head and neck squamous cell carcinoma (HNSCC) is required to select patients for clinical follow up from those who require surgical treatment. The difficulty in determining the significance of residual masses post-treatment limits the utility of anatomical imaging with CT and/or MRI [ The negative predictive values (NPV) of response assessment FDG PET-CT have been shown to be excellent, identifying patients who do not require surgical intervention [6][7][8][9][10][11][12][13][14]. This applies even in the context of metabolically inactive residual masses [8; 15].…”
mentioning
confidence: 99%
“…When there is doubt about clinical and radiological response a 'second-look' PET-CT can be used to spare patients unnecessary surgical intervention Introduction Accurate response assessment following (chemo)radiotherapy for head and neck squamous cell carcinoma (HNSCC) is required to select patients for clinical follow up from those who require surgical treatment. The difficulty in determining the significance of residual masses post-treatment limits the utility of anatomical imaging with CT and/or MRI [ The negative predictive values (NPV) of response assessment FDG PET-CT have been shown to be excellent, identifying patients who do not require surgical intervention [6][7][8][9][10][11][12][13][14]. This applies even in the context of metabolically inactive residual masses [8; 15].…”
mentioning
confidence: 99%
“…In other words, 18 FDG-PET/CT is an ideal modality to rule out residual disease after (chemo)radiotherapy. Recent studies demonstrated further increased accuracy with delayed image acquisition around 16 weeks after treatment with NPVs reaching 100% (6466). On the other hand, the access to 18 FDG-PET/CT in low-cost setting is not always warranted, and morphologic imaging alone with MRI or CT should be relied on.…”
Section: Resultsmentioning
confidence: 99%